2020
DOI: 10.1098/rsob.200263
|View full text |Cite
|
Sign up to set email alerts
|

Signalling through cerebral cavernous malformation protein networks

Abstract: Cerebral cavernous malformations (CCMs) are neurovascular abnormalities characterized by thin, leaky blood vessels resulting in lesions that predispose to haemorrhages, stroke, epilepsy and focal neurological deficits. CCMs arise due to loss-of-function mutations in genes encoding one of three CCM complex proteins, KRIT1, CCM2 or CCM3. These widely expressed, multi-functional adaptor proteins can assemble into a CCM protein complex and (either alone or in complex) modulate signalling pathways that influence ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 188 publications
(423 reference statements)
0
24
0
Order By: Relevance
“…However, the cellular type most strongly associated with cavernous malformations is the endothelial cell. The role played by CCM genes in other cellular models strictly associated with lesions localization (i.e., neuronal cells, astrocytes, pericytes, and smooth muscle cells) is unknown, and there is no evidence about their direct contributions to CCM pathology [ 45 ]. There is probably a tight interplay between endothelial cells and the glia in the central nervous system (CNS), which may explain why mutations in CCM-related genes are followed by the appearance of lesions predominantly localized in the brain and spinal cord [ 46 ].…”
Section: Ccm Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cellular type most strongly associated with cavernous malformations is the endothelial cell. The role played by CCM genes in other cellular models strictly associated with lesions localization (i.e., neuronal cells, astrocytes, pericytes, and smooth muscle cells) is unknown, and there is no evidence about their direct contributions to CCM pathology [ 45 ]. There is probably a tight interplay between endothelial cells and the glia in the central nervous system (CNS), which may explain why mutations in CCM-related genes are followed by the appearance of lesions predominantly localized in the brain and spinal cord [ 46 ].…”
Section: Ccm Proteinsmentioning
confidence: 99%
“…In 2005, Zawistowski et al [ 60 ] reported that the subcellular localization of KRIT1 is differentially influenced by these two proteins—if ICAP1α induces nuclear translocation, CCM2 maintains KRIT1 into the cytosol. However, it has been recently suggested that the whole complex ICAP1α/KRIT1/CCM2 shuttles back and forth from cytoplasm to nucleus and plays different roles in different cellular compartments [ 45 ].…”
Section: Ccm Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation rates for each gene range between 53% and 65% for KRIT1/CCM1, 15% and 19% for CCM2, and 10% and 16% for CCM3 [9,10] . However, genotype does not entirely explain the large clinical variability of CCM disease, even among family members carrying the same mutation, suggesting that genetic and environmental modifiers can contribute to CCM disease [11] . Despite the differences between families, some genotype-phenotype correlations are delineated.…”
Section: Introductionmentioning
confidence: 98%
“…The clinical approach to CCM disease depends on the position and size of the lesions and its association with hemorrhages or intractable seizures. When possible, the microsurgical resection of lesions is the eligible route [11,24] . Therefore, the development of new pharmacological strategies is necessary to prevent lesion formation and for treating patients with severe inoperable disease or with multiple lesions.…”
Section: Introductionmentioning
confidence: 99%